Wet-chemical synthesis of hexagonal plate-like niobate particles for lead-free piezoceramics. Issue 8 (1st June 2018) - Bai, Shan; Zhang, Jian; Chen, Zhuwen; Wang, Yanding; Dong, Lei; Chen, Chao; Yan, Yiyong; Hong, Mei
Abstract: Hexagonal plate-like potassium-sodium niobate (KNN) perovskite particles with average width of 5.8 µm, thickness of 0.5 µm, and high aspect ratio over 10 were successfully prepared via low temperature surfactant-free wet-chemical synthesis and subsequent calcination. Forming potassium rich hydrate particles was a crucial step for modulating the plate-like morphology with well-defined hexagonal outline and uniform size distribution, the aspect ratio of which increased with increasing potassium content. Removal of crystal water in the KNN-hydrate took place at 150–250 °C and the weight loss was approximately 9%. The K + /Na + ratio of the perovskite KNN plates obtained by calcination was consistent with the starting stoichiometry. This low-temperature wet-chemical synthesis route to KNN is expected to pave a low-cost scalable way for the mass production of plate-like template particles in the field of high-performance lead-free textured piezoceramics.